Eslicarbazepine acetate: An efficacy and safety as an antiepileptic drug in clinical trials and open studies - Stefaniak, Martyna; Pietrzak, Zofia; Dzikowski, Piotr; Nowicka, Emilia; Obel, Michał; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Eslicarbazepine acetate (Zebinix®, ESL), a voltage-gated sodium channel blocker, is a once-daily, orally administered anti-seizure medication available in the EU for use as monotherapy in adults with newly diagnosed partial-onset seizures and as adjunctive therapy in adults, adolescents, and children aged > 6 years with partial-onset seizures. It was approved by the European Medicines Agency and launched onto the European market in 2009. This study aimed to assess the efficacy and safety of ESL in the treatment of focal-onset seizures. Our study material consisted of publications, which were found in PubMed, Google Scholar, and Embase databases. In order to find the proper publications, the search has been conducted with the use of a combination of keywords like: “eslicarbazepine acetate", "focal-onset seizures treatment", "epilepsy treatment", "eslicarbazepine acetate pharmacokinetics”. The first step was to find proper publications from the last 10 years. The second step was to carry out an overview of the found publications. Results of mentioned studies proved that for adults with medically uncontrolled partial-onset seizures, ESL monotherapy is well tolerated and effective over the long term, including the patients who transitioned from CBZ-CR monotherapy. Adjunctive ESL demonstrated a sustained therapeutic effect and was well-tolerated, safe, and efficacious during the treatment of adults with partial-onset seizures. Both 800 mg and 1200 mg once-daily doses were well tolerated. Moreover, significant improvements in depressive symptoms and quality of life domains were observed under long-term treatment with ESL.